LEARNING PRINCIPLE OF WORKING OF PHOTO COLORIMETER - O’sarov Azamat Asatullayevich; Sunnatova Farangiz Akbar qizi; Sunnatullayeva Nigina Djurabekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we talk about principle of colorimeter, working of colorimeter, parts of colorimeter.